CHALLENGES IN CONSTRUCTING DIALOGIC PRACTICES: INSIGHTS FROM B.ED. CLASSROOMS - Sadia Bano; Shahzada Qaisar; Intzar Hussain Butt (International Journal of Contemporary Issues in Social Sciences, 2024)
The study examines the challenges faced by the teachers in constructing dialogic practices in the classroom. The research followed an interpretive paradigm with a qualitative approach, utilizing a case study method that included focus group interviews with four teachers. Findings highlight the complexities arising from diverse student backgrounds, perceptions of educational adequacy, and the integration of theoretical and practical learning amidst resource constraints. Communication issues from low English proficiency led teachers to consider using students’ first language, while inadequate classroom technology and training hindered technology integration. Despite these challenges, teachers promoted active participation and constructive feedback, recognizing the positive impact of dialogicity on student learning.